2020
DOI: 10.1021/acs.jmedchem.0c00826
|View full text |Cite
|
Sign up to set email alerts
|

Nature-Inspired (di)Azine-Bridged Bisindole Alkaloids with Potent Antibacterial In Vitro and In Vivo Efficacy against Methicillin-Resistant Staphylococcus aureus

Abstract: Natural bisindole alkaloids such as Hyrtinadine A and Alocasin A, which are known to exhibit diverse bioactivities, provide promising chemical scaffolds for drug development. By optimizing the Masuda borylation–Suzuki coupling sequence, a library of various natural product-derived and non-natural (di)­azine-bridged bisindoles was created. While unsubstituted bisindoles were devoid of antibacterial activity, 5,5′-chloro derivatives were highly active against methicillin-resistant Staphylococcus aureus (MRSA) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 41 publications
5
28
0
Order By: Relevance
“…The antimicrobial activity of marine alkaloids was also reported in the study carried out by Rehberg et al [ 41 ] with methicillin-resistant Staphylococcus aureus . These authors observed significant reductions in the size and microbial counts in contaminated skin wounds of animals treated with either 3,3′-(pyrimidine-2,5-diyl)bis(5-chloro-1H-indole) ( 39 ) or 2,6-bis(5-chloro-1H-indol-3-yl)pyridine ( 40 ) after 12 days.…”
Section: Marine Alkaloids With Biological Activity In Vivosupporting
confidence: 53%
See 2 more Smart Citations
“…The antimicrobial activity of marine alkaloids was also reported in the study carried out by Rehberg et al [ 41 ] with methicillin-resistant Staphylococcus aureus . These authors observed significant reductions in the size and microbial counts in contaminated skin wounds of animals treated with either 3,3′-(pyrimidine-2,5-diyl)bis(5-chloro-1H-indole) ( 39 ) or 2,6-bis(5-chloro-1H-indol-3-yl)pyridine ( 40 ) after 12 days.…”
Section: Marine Alkaloids With Biological Activity In Vivosupporting
confidence: 53%
“…Other relevant synthetic alkaloids are 3,3′-(pyrimidine-2,5-diyl)bis(5-chloro-1H-indole) ( 39 ) and 2,6-bis(5-chloro-1H-indol-3-yl)pyridine ( 40 ) [ 41 ]. The synthesis of 3,3′-(pyrimidine-2,5-diyl)bis(5-chloro-1H-indole) ( Figure 12 A; compound 39 ) was possible with a one-pot reaction composed of three steps initiated with 5-chloro-3-iodoindole ( 102 ).…”
Section: Chemical Modification and Synthesis Of Marine Alkaloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study indicated that Gram-positive bacteria are more susceptible than Gramnegative to the antibacterial activity of bis-indoles [21]. It had been postulated that the outer membrane composition of Gram-negative bacteria may restrict bis-indole interaction and permeability [21].…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that the antibacterial activity of three natural bis-indoles, isolated from the sponge Topsentia pachastrelloides was due to the inhibition of MRSA pyruvate kinase (PK), an enzyme involved in carbohydrate metabolism [18]. However, a study on synthetic analogues and modified derivatives of bis-indoles originally isolated from the medicinal plant Alocasia macrorrhiza and sponge Hyritos sp., suggested that the antibacterial activity of these bis-indole alkaloids against MRSA is independent of PK inhibition and is instead due to the disruption of the cell membrane [21].…”
Section: Introductionmentioning
confidence: 99%